2007
DOI: 10.1593/neo.07358
|View full text |Cite
|
Sign up to set email alerts
|

CITED1 Expression in Wilms' Tumor and Embryonic Kidney

Abstract: Wilms' tumors, or nephroblastomas, are thought to arise from abnormal postnatal retention and dysregulated differentiation of nephrogenic progenitor cells that originate as a condensed metanephric mesenchyme within embryonic kidneys. We have previously shown that the transcriptional regulator CITED1 (CBP/p300-interacting transactivators with glutamic acid [E]/aspartic acid [D]-rich C-terminal domain) is expressed exclusively in these nephrogenic progenitor cells and is downregulated as they differentiate to fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 40 publications
5
42
0
Order By: Relevance
“…Failure in FGF/EGF feedback control by genes such as Sprouty might contribute to the undifferentiated metanephric blastema found in Wilms' tumor, where the advanced stage of the disease is known to be correlated with persistent expression of early blastemal markers such as Cited1 and Meox1 (Williams et al, 2004;Li et al, 2005;Lovvorn et al, 2007a;Lovvorn et al, 2007b). The FGF/EGF signaling pathway components that are disrupted by Spry1, or genes that alter Spry1 activity, might represent novel therapeutic targets to combat Wilms' tumor and other cancers that arise from parent stem cells that normally display a requirement for FGF signaling during self-renewal.…”
Section: Research Articlementioning
confidence: 99%
“…Failure in FGF/EGF feedback control by genes such as Sprouty might contribute to the undifferentiated metanephric blastema found in Wilms' tumor, where the advanced stage of the disease is known to be correlated with persistent expression of early blastemal markers such as Cited1 and Meox1 (Williams et al, 2004;Li et al, 2005;Lovvorn et al, 2007a;Lovvorn et al, 2007b). The FGF/EGF signaling pathway components that are disrupted by Spry1, or genes that alter Spry1 activity, might represent novel therapeutic targets to combat Wilms' tumor and other cancers that arise from parent stem cells that normally display a requirement for FGF signaling during self-renewal.…”
Section: Research Articlementioning
confidence: 99%
“…The tumors are characterized by blastemal, epithelial and stromal elements much like the developing kidney. The blastema displays nephron progenitor-like characteristics, expressing factors such as CITED1, SIX1 and SIX2 (Li et al, 2002;Lovvorn et al, 2007;Murphy et al, 2012;Sehic et al, 2012Sehic et al, , 2014. Mutations in the DNA binding homeodomain of SIX1 and SIX2 are associated with chemotherapy-resistant blastemas, suggesting that these mutations might contribute to an aggressive etiology of such tumors (Wegert et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…CD56 (NCAM), which has been proposed to be specific for the blastemal compartment of WT (Roth et al, 1988;Muir et al, 2001), was not observed in any WT culture, while all primary cells expressed CITED1, another proposed blastemal marker (Lovvorn et al, 2007). Cytokeratin staining (Cam5.2), which is specific for the epithelial component of WT tissue, distinguished two types of WT cultures (Fig.…”
Section: Primary Wt Culturesmentioning
confidence: 87%